Control system for a tensile-testing device using low-cost hardware and open-source software - Kranjec, Matej (Strojniški vestnik, 2020)
The aim of this study is to verify whether a Raspberry Pi 3 B+ can be utilized as a low-cost device for controlling a tensile-testing device used for material research purposes. A list of requirements based on already-available hardware was drawn up, which the new control system had to fulfil. To connect all the necessary equipment, a connection board was constructed, and some additional hardware was acquired for the system to be able to perform all the necessary tasks. The whole controlling system was also put in a small enclosure to make it portable. The control-system software was written in C++ using the Pigpio library. The developed system was then tested, and the results were compared to a commercially available Instron 8802 device. A comparison of the results shows that the upgraded equipment can produce comparable results to commercially available devices and is sufficiently accurate to be applied for research purposes for the characterization of soft tissues and other materials.
Keywords: krmilni sistemi; low-cost; measuring equipment; merilna oprema; natezne naprave; nizkocenovna strojna oprema; odprtokodno; Raspberry Pi; tensile testing